An Evaluation of Driverless Haul Truck Incidents on a Mine Site: A Mixed Methodology - Pascoe, Todd (Curtin University, 2020)
The thesis was the first evaluation of driverless haul truck incidents on a mine site by describing the factors that led to a loss of control. A mixed methodology was used to evaluate safety incidents by comparing incident causes to the experiences of mineworkers interacting with the autonomous system. The research explains the safety transformations that occurred on the mine site and provides a way forward for its safe use in the WA Mining Industry.